Factors That Affect the Quality Of Vocational Education Graduates in the 4.0 Era: Job Readiness, Skills and Digital Services - Ade Irfansyah; Suparji; Bambang Suprianto; Cris Kuntadi; Heri Sudarmaji (Dinasti Publisher, 2023)
Vocational education is an education that provides technical skills, knowledge and abilities needed by the workforce in various industrial sectors, but currently there are many graduates who are not accepted to work in the industrial sector, including because the graduates do not have the quality that adequate according to industry standards. The purpose of this study is to find out several factors that affect the quality of graduates. This research method is a literature review taken from several digital search sources of scientific journals such as the Garuda website, Researchgate and Google Scholar. The results obtained are that the factors that affect the quality of graduates are: (1) job readiness, (2) skills, and (3) digital service capabilities. Meanwhile, several other factors that need to be made for further studies are factors (1) disciplinary attitude, (2) independence, and (3) academic achievement.